Elizabethan globalism England, China and the rainbow portrait - Dimmock, Matthew 1975- (Paul Mellon Centre for Studies in British Art, 2019)
A fascinating look at how Elizabethan England was transformed by its interactions with cultures from around the world. Challenging the myth of Elizabethan England as insular and xenophobic, this revelatory study sheds light on how the nation's growing global encounters-from the Caribbean to Asia-created an interest and curiosity in the wider world that resonated deeply throughout society. Matthew Dimmock reconstructs an extraordinary housewarming party thrown at the newly built Cecil House in London in 1602 for Elizabeth I where a stunning display of Chinese porcelain served as a physical manifestation of how global trade and diplomacy had led to a new appreciation of foreign cultures. This party was also the likely inspiration for Elizabeth's celebrated Rainbow Portrait, an image that Dimmock describes as a carefully orchestrated vision of England's emerging ambitions for its engagements with the rest of the world. Bringing together an eclectic variety of sources including play texts, inventories, and artifacts, this extensively researched volume presents a picture of early modern England as an outward-looking nation intoxicated by what the world had to offer